2018
DOI: 10.5713/ajas.17.0779
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association study of fatty acid composition in Duroc swine

Abstract: ObjectiveGenome wide association study was conducted to identify and validate candidate genes associated with fatty acid composition of pork.MethodsA total of 480 purebreed Duroc pigs were genotyped using IlluminaPorcine60k bead chips while the association test was implemented following genome-wide rapid association using Mixed Model and Regression-Genomic Control (GRAMMAR-GC) approach.ResultsA total of 25, 29, and 16 single nucleotide polymorphisms (SNPs) were significantly associated with stearic (18:0), ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A similar QTL signal was detected on SSC12, where the FASN gene was located, on GWAS performed for the abundance of C14:0 in adipose tissue and muscle in Erhualian and Duroc pigs 21,23 . The signal found on SSC14 for the percentages of C16:0, C16:1(n-7), C18:0, C18:1(n-9), SFAs, and MUFAs was also found on GWAS performed in different pig populations for FA composition in adipose tissue and IMF, which reported SCD and ELOVL3 as candidate genes [19][20][21][22][23][24][25][26] . On a previous study in the BC1_LD animals, the FADS genes were proposed as potential candidate genes for the SSC2 QTL associated with the percentages of C16:1(n-9), C18:2(n-6), C18:3(n-3), and PUFAS in backfat 109 .…”
Section: Ld5mentioning
confidence: 60%
See 2 more Smart Citations
“…A similar QTL signal was detected on SSC12, where the FASN gene was located, on GWAS performed for the abundance of C14:0 in adipose tissue and muscle in Erhualian and Duroc pigs 21,23 . The signal found on SSC14 for the percentages of C16:0, C16:1(n-7), C18:0, C18:1(n-9), SFAs, and MUFAs was also found on GWAS performed in different pig populations for FA composition in adipose tissue and IMF, which reported SCD and ELOVL3 as candidate genes [19][20][21][22][23][24][25][26] . On a previous study in the BC1_LD animals, the FADS genes were proposed as potential candidate genes for the SSC2 QTL associated with the percentages of C16:1(n-9), C18:2(n-6), C18:3(n-3), and PUFAS in backfat 109 .…”
Section: Ld5mentioning
confidence: 60%
“…As some of the QTL signals found in our study were previously reported in other GWAS for FA composition in adipose tissue and muscle in several swine populations 16 26 , we decided to genotype polymorphisms in the most recurrent candidate genes reported in these studies: FADS2 , FASN , ELOVL6 , ELOVL7 and SCD . A total of 21 SNPs were genotyped among these positional candidate genes.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Inter- and intra-breed differences are well known in terms of total IMF variability, with very obvious cases of genetic groups with higher marbling [ 127 , 128 ], while populations selected for other traits correlated to total fat, such as lean meat yield, have seen a decrease in IMF as a negative side effect [ 129 , 130 , 131 ] Studies show a medium to high heritability not only for total IMF, but also for the majority of fatty acid groups which can be endogenously synthesized in both ruminants and monogastrics [ 132 , 133 ]. According to GWAS studies in different species, both total IMF and fatty acid composition in meat are influenced by key regulatory genes with major effects and multiple genes with smaller effects, and have shown moderate to high heritability estimates for IMF and low to medium heritability for specific fatty acids [ 134 , 135 , 136 , 137 , 138 , 139 ]. However, despite the potential to include IMF fatty acids in breeding programs, antagonistic genetic relationships with performance have usually minimized the emphasis on selection for these traits.…”
Section: Manipulating the Nutritional Value Of Red Meatmentioning
confidence: 99%
“…The genome-wide association studies (GWAS) make it possible to study over one-hundred thousand individual nucleotides (SNP) (Pearson et al, 2008). As a result of GWAS, several illnesses associated genes, genes associated with economically important properties and genes associated with various metabolic and biological functions have been identified (Viterbo et al, 2018). The fatty acid composition of Duroc swine showed that saturated fatty acids (SFA) and mono-unsaturated fatty acids (MUFA) are highly heritable, according to genetic estimations they are at 0.50-0.57, while polyunsaturated fatty acids (PUFA) are moderately at between 0.25 and 0.46.…”
Section: Genotypingmentioning
confidence: 99%